Millennials' Attitudes Towards Organic Personal Care Products in South Africa: An Application of the Theory of Planned Behaviour - Lupindo, Mongezi (School of Management Studies, 2021)
The organic products market has grown worldwide in recent years. Increasing demand for products that are less harmful to the environment and health is one of the factors driving this phenomenon. Consumers are becoming more conscious than ever before about the environmental effects of the products they consume. Specifically, millennials have become environmentally responsible consumers. Although earlier studies have provided insights into factors influencing attitudes towards organic products in various contexts, there is limited research into organic products in the South African context, specifically research focusing on organic personal care products among millennials. Millennials are influential consumers who are environmentally conscious and digitally savvy. Recently, social media has gained increased attention for its ability to amplify environmental concerns and promote sustainable behaviour among young people. As a result, understanding how young consumers develop their purchasing behaviours towards organic personal care products is necessary. Therefore, this study investigated millennials' attitudes towards environmental issues and health consciousness, and the effects of their attitudes, social norms, and perceived behavioural controls on their willingness to pay for organic personal care products. The study followed a descriptive, quantitative research design using an online selfadministered survey. A non-probability virtual snowball sample of 433 Facebook users, aged between 18 and 25 years who live in South Africa, was followed. Out of the 433 questionnaires that were collected, 377 were included for analysis. Data were analysed using Structural Equation Modelling (SEM). The results reveal that South African millennials' environmental concern and health consciousness had a significantly positive influence on their attitudes towards organic personal care products. The results also showed that attitude towards organic personal care products had a significant positive effect on subjective norms, and attitude was the strongest significant predictor of willingness to pay for organic personal care products. The results provide marketers with insights into how millennials ' attitude and willingness to buy organic personal care products can be influenced. Specifically, marketers should develop marketing strategies that incorporate environmental concerns, health awareness, and social influence to increase customer willingness to pay for organic personal care products. The findings also help policymakers understand the level of customer concern about the environment and their health, develop effective environmental policies necessary to achieve sustainability, and boost green purchasing through legislation. In addition, policymakers should be more constructive to promote ecologically conscious consumer behaviour. Collaborating with the private sector in various campaigns would help to enhance consumers' attitudes regarding the environmental concern.